CONVENTIONAL MODELLING APPROACH TO PREDICT THE DYNAMICS OF COVID-19 (FUDMA JOURNAL OF SCIENCES, 2021)
The study examined transmission dynamics of COVID-19 with conventional modelling approach. We developed a mathematical model for COVID-19 pandemic as SEQIR where I, the infected compartment is partitioned in to  and for reported and unreported group of infected individuals. Basic reproduction number has been obtained and the stability analysis was carried out. The results revealed that the disease may die out in time
Keywords: COVID-19, Mathematical Modelling, Transmission Dynamics, infectious disease, Predict, Conventional